RESEARCH ON THE MATERIAL CHARACTERISTICS OF WOVEN CARBON FIBER COMPOSITE SQUARE TUBES UNDER THREE-POINT BENDING LOAD (MT) - CHEN Guang; FENG YuPeng; XIE DongXuan; XIAO Sen; JING GuoXi (Jixie qiangdu)
Under the bending load generated by automobile collision, the composite safety components should have the ability to resist deformation and dissipate crashworthiness energy. In order to determine the mechanical parameters of the progressive damage material model of a woven carbon fiber composite thin-walled beam in the three-point bending condition, the mechanical properties test of the woven carbon fiber composite material and the three-point bending experiment of square tubes made by this material were carried out, thus got the basic mechanical parameters, bending failure history and force-deformation characteristics. Then the effects of the non-test parameter in the progressive damage material model on the simulation results were analyzed and the effectiveness of the multilayer shell modeling method were discussed. By comparing with the experimental results, the non-experimental parameters and effective simulation modeling methods for the progressive damage model of composite materials were gotten. The obtained material properties can be used for the crashworthiness simulation analysis of this material structure in similar working conditions.